Real-World Evidence for Favourable Quality-of-Life Outcomes in Hungarian Patients with Relapsing-Remitting Multiple Sclerosis Treated for Two Years with Oral Teriflunomide: Results of the Teri-REAL Study - Krisztina Bencsik; Enikő Dobos; Zita Jobbágy; Adrienne Jóri Birkás; Krisztina Kovács; Mária Sátori; Gyula Lencsés; Gabor Bartok; Erika Losonczi; László Vécsei; on behalf of the Teri-REAL Investigators (MDPI AG, 2022)
Relapsing-remitting multiple sclerosis (RRMS) is a degenerative, inflammatory disease of the central nervous system in which symptoms and disability progression vary significantly among patients. Teri-REAL was a prospective, real-world observational study that examined quality-of-life (QoL) and treatment outcomes in a Hungarian cohort of RRMS patients treated with once-daily oral teriflunomide. QoL was assessed at baseline, 12, and 24 months with the Multiple Sclerosis Quality of Life-54 (MSQoL-54) questionnaire. Other measurements included disease progression (Patient Determined Disease Steps [PDDS]), clinical efficacy (relapses), fatigue (Fatigue Impact Scale [FIS]), depression (Beck Depression Inventory [BDI]), cognition (Brief International Cognitive Assessment in MS [BICAMS]), persistence and safety. 212 patients were enrolled (69.1% female, 50.5% treatment naïve), with 146 (69%) completing the study. Statistically significant improvements in subscales of the MSQoL-54 versus baseline were found at Month 12 and Month 24. Significant improvements were also observed for individual components of the BICAMS score at 24 months, while PDDS, FIS and BDI scores remained stable. The mean annualised relapse rate was 0.08 ± 0.32. There were 93 safety events, most of which were mild to moderate. Improved QoL and cognitive outcomes in teriflunomide-treated patients over 2 years offer a unique perspective to this real-world study.